Factors affecting Chinese university students’ intention to continue using virtual and remote labs - Zhang, Mu-Hua; Su, Chien-Yuan; Li, Yan; Li, Yan-Yan (Australasian Journal of Educational Technology, 2020)
Recently, virtual and remote labs (VRLs) have been developed to support students in conducting experiments in engineering and science education. However, little is known about the students’ intentions to continue using VRLs and their satisfaction with the experience. This study proposed an extended model embedded within the expectation confirmation model and two variables concerning flow experience (time distortion and focused attention) to predict Chinese university students’ satisfaction with and intention to continue using VRLs. A structural equation modelling technique based on covariance was conducted to evaluate survey questionnaire responses received from 238 students at a university located in central China. The results demonstrated that satisfaction was the most crucial determinant of the students’ intention to continue using VRLs, followed closely by perceived usefulness. Confirmation played an indirect role in predicting students’ intentions to continue using VRLs via satisfaction and perceived usefulness. Students’ flow experience while performing virtual experiments played a positive and direct role in confirming their expectations of VRLs.